(3eQGJH GdNdbs
(3ChdgG (B:s
(3hgh eQGJH GdNdb ajg GYde Gf GdcKH (B( (3GdcJH (B) (3gh eSc GHjV ai LfI YOf hLfI YOf gi bUHI GdLfI s
(3BNQgG (B:s
(3hefge GdeDKQ HeLehY Gdcd hefge GdeDKQ HeLehY GdHYV JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs